Impact of a Cybersecurity Work-Related Course on Students' Career Thoughts and Attitudes: A PISCES Course Evaluation (Journal of The Colloquium for Information Systems Security Education, 2024)
This article proposes a research study conducted at Murray State University Cybersecurity and Network Management program to investigate the impact of work-related experiential learning on college students' career thoughts and attitudes within the context of cybersecurity career development. The Cybersecurity and Network Management program introduced the CNM 518 course based on the Public Infrastructure Security Cyber Education System (PISCES) project that offers practical, hands-on experiences. The proposed research project slated for Spring 2024, aims to assess how this work-related experiential learning influences students' career thoughts and attitudes, using the Career Thoughts Inventory as a measurement tool. This research project emphasizes the importance of reflective learning within CNM 518 and aims to contribute empirical evidence on the impact of work-related experiential learning on students' career thoughts and how such learning experiences positively influence the career decision-making processes and, subsequently, the broader field of cybersecurity education.
Keywords: PISCES; Career Development; Work-Related Experiential Learning; Cybersecurity; Security Operation Center